P6 MICRA AV AS AN INNOVATIVE THERAPEUTIC OPPORTUNITY IN PATIENTS WITH A PAROXYSMAL ATRIOVENTRICULAR BLOCK OR AN ADVANCED OR PERSISTENT TYPE II 2ND–DEGREE ATRIOVENTRICULAR BLOCK. (18th May 2022) - Dentico, A; Ferrieri, A; Epicoco, G; Troccoli, R; Carretta, F; D'Agostino, C; Carretta, D
Abstract: Introduction: Micra AV is the technological evolution of Micra VR. It's a monocameral leadless pacemaker that works like a VDD PM, synchronizing atrial activity with the ventricular one. The purpose of the study is to evaluate the response of Micra AV in patients with a paroxysmal atrioventricular block, in which a low percentage of stimulation is expected, and in patients with AVB with normal atrial activity. Materials and Method: From August 2020 to June 2021 in our center were implanted 11 Micra AV: 4 for advanced AVB, 3 for a paroxysmal AVB and 4 post–extraction. To all patients it was given remote monitoring to guarantee a constant remote follow–up. For each one, were analyzed the values measured at the implant's moment and those of periodic remote follow–ups, paying particular attention at the device's percentage of stimulation. Furthermore, a questionnaire was submitted to detect the psychophysical condition, the way in which the device interferes in everyday life, any physical pain, the emotional state, always correlating post–operative with the pre–operative. Particular attention was paid to the decrease in the incidence of adverse events or post–operative complications. In this way, it was possible to focus the study on 3 aspects: technician, quality of post–implant life and the device's approval. Results: All patients no longer presented syncopes during a follow–up ranging from a minimum of 5 to a maximum of 10 months. About the analysis made on the percentage of stimulation, the results were obtained by dividing patients into 2 groups based on the nature of the block. Almost all patients with advanced AVB presents a percentage of stimulation that doesn't exceed 20%; in subjects with paroxysmal AVB this remains below 2%. The results of the questionnaire instead show how the leadless PMs are more appreciated both for a lower aesthetic impact, and for minor functional consequences linked to the lack of catheters who often limit the patient. This results in a better patient–device relationship and better acceptance of the leadless device. Conclusions: The use of a Leadless PM in patients with syncope is still to be deepened and for this we will have to follow these patients over time to have a wider cases. A certain data is that these PMs are more appreciated as they have less impact on the quality of patients' life.